2014
DOI: 10.3390/su6084723
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Patterns and Policy Implications of Urban Land Expansion in Metropolitan Areas: A Case Study of Wuhan Urban Agglomeration, Central China

Abstract: Abstract:Relatively little attention has been paid to examining the spatial expansion features of cities at various tiers at the regional level in China, especially those located in central and western regions of the country. Based on Landsat satellite imagery from four years-1980, 1990, 2000, and 2010, this 1980-1990, 1990-2000, and 2000-2010 respectively, exhibiting significant fluctuation between the different periods studied. Geographically, this spatial expansion pattern was characterised by conspicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…The importance of understanding urbanization patterns is evidenced by the increasing number of studies around the world during the past few decades [5,6,[11][12][13][14][15][16][17]. For example, Dietzel et al Changes in landscape metrics measuring urbanization patterns on the basis of three hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of understanding urbanization patterns is evidenced by the increasing number of studies around the world during the past few decades [5,6,[11][12][13][14][15][16][17]. For example, Dietzel et al Changes in landscape metrics measuring urbanization patterns on the basis of three hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…This process is similar that which has occurred in Ho Chi Minh [2], Dhaka [1,[3][4][5][6]10], Delhi [7], Hanoi [8] and Ansan [9]. Numerous bare land areas emerging along with urbanization processes have cast irreversible impacts on the urban environment, such as air pollution and soil loss [51][52][53][54][55][56][57]. In the plum rain season, flash flooding hazards have become a serious issue and have caused human death and damages to urban infrastructure in the city [52], similar to that in Dhaka [3].…”
Section: Analyses On Urbanization Of Wuhanmentioning
confidence: 69%
“…Rapid growth of the economy is the primary cause for rapid urbanization, as economic opportunities in the city are fueling rural to urban migration on a massive scale [51]. Census data indicated that the urban GDP of Wuhan was only 17.76 billion dollars in 2000, which increased to 133.17 billion dollars in 2013, with an annual growth rate of 49.99% [42,43].…”
Section: Analyses On Urbanization Of Wuhanmentioning
confidence: 99%
See 1 more Smart Citation
“…Associated research topics are focused on remote sensing monitoring methods and simulation models, spatio-temporal characteristics and evolution laws, impacting factors and driving mechanisms, change effect assessment, and landscape structure optimization [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The simulation models employed for urban expansion and land use change include the Markov, CA (Cellular Automata)-Markov, ANN (Artificial Neural Network)-Markov, LTM (Land Transformation Model), ABM (agent-based model), CLUE-S, and SLEUTH models [18,19].…”
Section: Introductionmentioning
confidence: 99%